Nanocarrier system: An emerging strategy for bioactive peptide delivery - Zhang, Xu; Li, Xinshe; Zhao, Yunhao; Zheng, Qing; Wu, Qiang; Yu, Yougui (Frontiers in Nutrition, 2022)
Compared with small-molecule synthetic drugs, bioactive peptides have desirable advantages in efficiency, selectivity, safety, tolerance, and side effects, which are accepted by attract extensive attention of the researchers in food, medicine and other fields. However, unacceptable barriers including mucus barrier, digestive enzyme barrier, and epithelial barrier, cause the weakening or the loss of bioavailability and biostability of bioactive peptides. Nanos-carrier system for bioactive peptide delivery needs to be further probed. We provide a comprehensive update the application of versatile delivery systems for embedding bioactive peptides, including liposomes, polymer nanoparticles, polysaccharides, hydrogels and self-emulsifying delivery systems, and further clarifying their structural characterization, and advantages and disadvantages as delivery systems. It aims to provide a reference for the maximum utilization of bioactive peptides. It is expected to be an effective strategy for improving the bioavailability and biostability of bioactive peptide.